Influence of high-energy ball milling of the starting powder on the sintering; microstructure and oxygen permeability of Ba0.5Sr0.5Co0.5Fe0.5O3-d membranes - Gao, D.; Zhao, J.; Zhou, W.; Ran, R.; Shao, Zongping (2011)
The effect of high-energy ball milling (HEBM) of the starting material of crystalline Ba0.5Sr0.5Co0.5Fe0.5O3-d (BSCF) powders on the sintering and oxygen permeability of the corresponding ceramic membrane was systematically investigated. Two different methods of dry milling and wet milling in a liquid alcohol medium were investigated along with three ball milling times (1, 2 and 3h), two different types of starting powders, and three different sintering temperatures (1000, 1050 and 1100°C). XRD, SEM and oxygen permeation measurements were performed on as-prepared membranes. The experimental results showed that HEBM is an effective way to improve the sintering, microstructure and oxygen permeability of BSCF membranes. By optimizing the HEBM process, the relative density of BSCF membranes improved significantly; as a result, the oxygen permeation flux of BSCF membranes improved by about 20% in comparison to BSCF membranes whose starting powders were not ball milled. Thus, HEBM is a promising way to increase the performance of BSCF membranes for oxygen separation. © 2010 Elsevier B.V.